Charge disproportionation and the pressure-induced insulator?metal transition in cubic perovskite PbCrO3 - Cheng, Jinguang (2014)
The perovskite PbCrO3 is an antiferromagnetic insulator. However, the fundamental interactions leading to the insulating state in this single-valent perovskite are unclear. Moreover, the origin of the unprecedented volume drop observed at a modest pressure of P = 1.6 GPa remains an outstanding problem. We report a variety of in situ pressure measurements including electron transport properties, X-ray absorption spectrum, and crystal structure study by X-ray and neutron diffraction. These studies reveal key information leading to the elucidation of the physics behind the insulating state and the pressure-induced transition. We argue that a charge disproportionation 3Cr4+ → 2Cr3+ + Cr6+ in association with the 6s-p hybridization on the Pb2+ is responsible for the insulating ground state of PbCrO3 at ambient pressure and the charge disproportionation phase is suppressed under pressure to give rise to a metallic phase at high pressure. The model is well supported by density function theory plus the correlation energy U (DFT+U) calculations.